Comparing differences between psychological distress and physiological markers in first division football players - Naji, Farah Layth (2017)
This study aimed to determine the level of stress as measured through different stress measurement methods (DASS questionnaire, SIgA, pulse rate and oxygen saturation). The highest scores for depression, anxiety, stress, pulse rate was before the competition (M=8.365, SD=2.733), (M=8.689, SD=3.962), (M=10.068, SD=3.094), (M=63.27, SD=5.008) respectively. While for salivary IgA and oxygen saturation, the highest score was at resting time (M=112.147, SD=14.431), (M=98.3, SD=1.893) respectively. Descriptive method was used for data collection. Participants were 74 football players of all the first division clubs in Karbala, Iraq, aged between 18-22 years old. Depression, anxiety and stress were measured at three different time points (resting time, before the training, before the competition), while salivary IgA, pulse rate, and oxygen saturation measurement were measured through five different time points (resting time, before the training, after the training, before the competition, after the competition). Comparison of variables across time points using a one-way repeated measures ANOVA was significant for all variables except depression (depression: p=0.108, anxiety: p=0.018, stress:p=0.008, salivary IgA:p=0.001, pulse rate:p=0.001, oxygen saturation:p=0.001). It can be concluded that the combination of psychological distress and physiological markers can provide accurate measurements of stress.